A Bibliometric Analysis of Pyroptosis From 2001 to 2021 - Ma, Dan; Yang, Bin; Guan, Baoyi; Song, Luxia; Liu, Qiyu; Fan, Yixuan; Zhao, Lin; Wang, Tongxin; Zhang, Zihao; Gao, Zhuye; Li, Siming; Xu, Hao (Frontiers in Immunology, 2021)
Background: Pyroptosis is a new programmed cell death discovered in recent years. Pyroptosis plays an important role in various diseases. Nevertheless, there are few bibliometric analysis systematically studies this field. We aimed to visualize the research hotspots and trends of pyroptosis using a bibliometric analysis to help understand the future development of basic and clinical research. Methods: The articles and reviews regarding pyropyosis were culled from Web of Science Core Collection. Countries, institutions, authors, references and keywords in this field were visually analyzed by using CtieSpace and VOSviewer software. Results: A total of 2845 articles and reviews were included. The number of articles regarding pyroptosis significantly increased yearly. These publications mainly come from 70 countries led by China and the USA and 418 institutions. We identified 605 authors, among which Thirumaladevi Kanneganti had the most significant number of articles, and Shi JJ was co-cited most often. Frontier in immunology was the journal with the most studies, and Nature was the most commonly cited journal. After analysis, the most common keywords are nod like receptor family pyrin domain containing 3 inflammasome, apoptosis, cell death, gasdermin D, mechanism, caspase-1, and others are current and developing areas of study. Conclusion: Research on the pyroptosis is flourishing. Cooperation and exchanges between countries and institutions must be strengthened in the future. The related pathway mechanism of pyroptosis, the relationship between pyroptosis and other types of programmed cell deaths as well as the role of pyroptosis in various diseases have been the focus of current research and developmental trends in the future research.